(untitled) (Journal of Management & Business, 2025)
The significance of prescribing new drugs is widely recognized in marketing literature. However, the varied definitions and conceptual approaches to this concept make it ambiguous and hinder its comprehension. The different ways in which new drug prescription is conceptualized, stemming from its overlapping nature (behavior, attitude, and decision-making), obscure the complexities of new drug prescriptions, making it difficult to understand the concept fully. This paper aims to build upon the theoretical basis of the concept of new drug prescription by defining it and exploring its different conceptualizations. To achieve this, a comprehensive review of existing literature on new drug prescriptions is carried out. Three primary conceptualizations are identified in literature, and a more comprehensive conceptualization of the concept is proposed. Additionally, the key characteristics and the most relevant measurement of this concept are clearly outlined.